GAMBARAN PENDERITA OSTEOARTRITIS DI BAGIAN BEDAH RSUD ARIFIN ACHMAD PERIODE JANUARI 2011 - DESEMBER 2013 - Bunga Amilia Suari; Muhammad Ihsan; Laode Burhanuddin (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTOsteoarthritis (OA) is a musculoskeletal disease characterized by the destruction of joint cartilage and joint gap narrowing.This condition is one of the most frequent medical problems occur and cause symptoms in the elderly and middle-aged. Increased severity of osteoarthritis is influenced by several factors, the main factor is the regulation of chondrocytes in the extracellular matrix, genetic influences, local mechanical factors and inflammation.This study was conducted to determine the overview of osteoarthritis in the surgical hospitals Arifin Ahmad period January 2011 - December 2013 which include age, gender, chief complaint, the joints are attacked and treatment measures. This study is a descriptive study with retrospective method. This study used a total sampling method. The samples were all population osteoarthritis sufferers who met the inclusion criteria. The total number of samples was 198 cases.This study shows that the age group > 60 years (84 people) (42.4%) and women (126 people) (63.6%) are the most age and sex in patients with osteoarthritis. Joint pain (100%) is the highest main complaints in patients with osteoarthritis. Knee joints (83.3%) is the location of the highest occurrence of osteoarthritis. Most treatment measures given to people with osteoarthritis are medical and physiotherapy.Keywords: Osteoarthritis, Overview